Associations Between Relative Lower and Upper Body Strength and Hyperinsulinemia in US Adults: 1999-2002 and 2011-2014 NHANES - Churilla, James R; Boyer, William R; Richardson, Michael R; Williams, Charles C (Journal of strength and conditioning research, 2025)
Churilla, JR, Boyer, WR, Richardson, MR, and Williams, CC. Associations between relative lower and upper body strength and hyperinsulinemia in U.S. Adults: NHANES 1999-2002 and 2011-2014. J Strength Cond Res 39(2): e171-e175, 2025-Skeletal muscle (SM) is an insulin-sensitive tissue that aids in glucose homeostasis. Insulin resistance leads to chronic hyperglycemia and type 2 diabetes. Previous evidence suggests that greater SM strength and size improve insulin dynamics. The primary aim of this study was to examine the association(s) between relative lower and upper body strength and hyperinsulinemia in a nationally representative sample of US adults. Samples of adult (≥50 years) subjects in the 1999-2002 ( N = 1,097) and adults (≥20 years) in the 2011-2014 ( N = 2,576) National Health and Nutrition Examination Survey were used in the analyses. Significance was set at p ≤ 0.05 for regression models. Quartiles (Q) of relative lower body strength (RLBS [N·BMI -1 ]) and relative grip strength (RGS [kg·BMI -1 ]) were created. Hyperinsulinemia was calculated using the weighted 75th percentile of log-fasted insulin among adults without diabetes. Inverse dose-response relationships were found for decreasing prevalence estimates of hyperinsulinemia by increasing Q of both RLBS and RGS. Similar dose-response associations were revealed for increasing Q of both RLBS and RGS and mean insulin concentrations. Following adjustment for demographic and lifestyle variables, subjects in Q2, Q3, and Q4 of RLBS were found to have significantly lower odds of hyperinsulinemia (OR 0.58 [ P = 0.05], OR 0.38, OR 0.22 [ p < 0.05 for both], respectively). Subjects in Q2, Q3, and Q4 of RGS were also found to have lower odds of hyperinsulinemia (OR 0.30; OR 0.14; OR 0.05 [ p < 0.0001 for all]), respectively. These data suggest RLBS and RGS may both be favorably associated with insulin homeostasis.